Simulation of auto –tuning pid controller for dc motor using Ziegler-Nichols method - Aina Azliyana, Mohamad (2012)
Ziegler-Nichols method is one of the controller methods to control a system in industry. In this project, the Ziegler-Nichols (ZN) tuning method was implemented a Proportional-Integral-Derivative (PID) controller to control a DC motor. There are so many application PID controller use is more than 90% of closed loop and open loop of industrial process The main objective is conducted numerous experiments and proposed rules for determining values of Kp,Ki,and Kd based on the transient step response of a plant. In this project, ZN rule is implement to PID controller transfer function and analysing the response of DC motor with PID controller. For this case, the objective representing the DC motor performance which is speed of the DC motor. The speed of the DC motor is identified by the input voltage of the motor and the output will be compared with the input. In this project, ZN and ES method was implemented in the PID system. The DC motor state space is derived to find the transfer function. The PID controller system circuit is then designed using MATLAB software. This is followed by the manual tuning of PID controller which is stimulated by using the Ziegler-Nichols method. The result of the project is known the better response of performance by Ziegler-Nichols rule.